Tackling pest-induced post-harvest loss under climate change - Odjo, Sylvanus; Quellhorst, Hannah E. (DLG-Verlag GmbH, 2024)
Insects are one of the most important factors in post-harvest losses world-wide. In the face of climate change, it is necessary to monitor the invasion pathways of these pests and adapt control strategies to minimise their negative impact on food grains. Our authors provide information on some of the most important pest species and their characteristics, as well as the state of research in this area.